Histerectomía total vía abdominal: revisión de la literatura - González A, Tomás; Parra M, Rodrigo; San Martín O, Alfredo; Salinas P, Hugo (Revista Hospital Clínico Universidad de Chile, 2021)
Hysterectomy is the most common gynecological surgery in non-pregnant women. There are different surgical approaches for total hysterectomy, abdominal, vaginal, laparoscopic and robotic routes. The choice is determined by different factors such as uterine size,malformations, surgical risks, skill of the surgeon, expected postoperative quality of life, and monetary costs. The surgical technique is well described in the literature, however, there are certain anatomical and functional considerations that must be known before performing the hysterectomy to avoid complications. The most frequent complications are hemorrhage, infections, thromboembolism, urinary and gastrointestinal tract injuries. Majority can be avoided with an adequate procedure and management of pre-existing comorbidities.